Design, physicochemical characterization, and optimization of organic solution advanced spray-dried inhalable dipalmitoylphosphatidylcholine (DPPC) and dipalmitoylphosphatidylethanolamine poly(ethylene glycol) (DPPE-PEG) microparticles and nanoparticles for targeted respiratory nanomedicine delivery as dry powder inhalation aerosols - Meenach, Samantha A (Dove Medical Press, 2013)
Novel advanced spray-dried and co-spray-dried inhalable lung surfactant-mimic phospholipid and poly(ethylene glycol) (PEG)ylated lipopolymers as microparticulate/nanoparticulate dry powders of biodegradable biocompatible lipopolymers were rationally formulated via an organic solution advanced spray-drying process in closed mode using various phospholipid formulations and rationally chosen spray-drying pump rates. Ratios of dipalmitoylphosphatidylcholine (DPPC) and dipalmitoylphosphatidylethanolamine PEG (DPPE-PEG) with varying PEG lengths were mixed in a dilute methanol solution. Scanning electron microscopy images showed the smooth, spherical particle morphology of the inhalable particles. The size of the particles was statistically analyzed using the scanning electron micrographs and SigmaScan(®) software and were determined to be 600 nm to 1.2 μm in diameter, which is optimal for deep-lung alveolar penetration. Differential scanning calorimetry (DSC) and powder X-ray diffraction (PXRD) were performed to analyze solid-state transitions and long-range molecular order, respectively, and allowed for the confirmation of the presence of phospholipid bilayers in the solid state of the particles. The residual water content of the particles was very low, as quantified analytically via Karl Fischer titration. The composition of the particles was confirmed using attenuated total-reflectance Fourier-transform infrared (ATR-FTIR) spectroscopy and confocal Raman microscopy (CRM), and chemical imaging confirmed the chemical homogeneity of the particles. The dry powder aerosol dispersion properties were evaluated using the Next Generation Impactor™ (NGI™) coupled with the HandiHaler(®) dry powder inhaler device, where the mass median aerodynamic diameter from 2.6 to 4.3 μm with excellent aerosol dispersion performance, as exemplified by high values of emitted dose, fine particle fraction, and respirable fraction. Overall, it was determined that the pump rates defined in the spray-drying process had a significant effect on the solid-state particle properties and that a higher pump rate produced the most optimal system. Advanced dry powder inhalers of inhalable lipopolymers for targeted dry powder inhalation delivery were successfully achieved.